PREVENTIVE EFFECT OF NIGELLA SATIVA L. AGAINST CEREBRAL OXIDATIVE ALTERATIONS INDUCED BY A HIGH-FAT, IRON-ENRICHED DIET IN MICE - benabdallah, halima; Rachida, Benaraba; Mostefa, Belarbi; Hemida, Houari (Food and Feed Research, 2025)
Recent research underscores the pivotal role of oxidative stress in cerebral alterations, prompting investigations into strategies such as the utilization of natural substances derived from medicinal plants, including Nigella sativa L. (NS) for their therapeutic potential. NS is known for its bioactive compounds that play a significant role in disease prevention and treatment. This study employed Fourier Transform Infrared Spectroscopic (FT-IR) analysis to identify functional groups and compounds in NS seed and to examine its preventive effects on cerebral oxidative changes induced by a high-fat diet (HFD) supplemented with iron in NMRI mice. The focus was on lipid oxidation, Ferric Reducing Antioxidant Power (FRAP), thiol groups, catalase activity, and Reduced Glutathione (GSH) levels. Mice were randomly assigned to four experimental groups (six mice per group): control (ST), control + NS seed powder (ST+NSP), high-fat diet with FeCl₃ (HFD/Fe3+), and HFD/Fe3+ + NSP. Following an 11-week experimental period, lipid oxidation, FRAP, thiol groups, and CAT activity were measured in plasma and brain, while GSH levels were assessed exclusively in the brain. NS significantly reduced lipid peroxidation in HFD/Fe3+ mice and restored FRAP, thiol groups, CAT activity, and GSH levels, which were markedly reduced in HFD/Fe3+ mice compared to the ST group. The HFD/Fe3+ regimen increased lipid peroxidation products relative to the ST group. These findings suggest that NSP supplementation mitigates cerebral oxidative stress and enhances antioxidant enzyme activity.
Keywords: black cumin; lipid oxidation; oxidative stress; hyperlipidic diet; FeCl3; brain alterations